VOCATIONAL EDUCATION QUALITY ASSURANCE ON THE BASIS OF PUBLIC-PRIVATE PARTNERSHIP (Innovative professional education, 2025)
Based on the analysis of legislative acts and regulatory documents, the concept of «quality of vocational education» and the components of the system of its assurance are characterized; taking into account the modern needs of consumers of educational services, attention is focused on the features of determining the guidelines for the functioning of the internal quality assurance system in vocational education institutions on the basis of principles, management technologies and mechanisms of public-private partnership
Keywords: quality of education, quality of vocational education, consumers of educational services, system of internal quality assurance in vocational education institutions, public-private partnership